Residents' perceptions of the environmental and social impact of tourism in rural areas - Liasidou, Sotiroula; Stylianou, Christiana; Berjozkina, Galina; Garanti, Zanete (My University, 2021)
Purpose This paper aims to provide an understanding of residents' perceptions of how tourism activity in a rural area impacts their environment as well as their economic and social lives individually and as a community. Design/methodology/approach As a primary method of data collection, semi-structured interviews were conducted with 20 residents in the rural areas of Cyprus. Findings The study's findings suggest that tourism activity in the rural areas provides a plethora of opportunities to residents, but comes with challenges and threats. Both social and environmental impacts are mainly for the benefit of the local communities as the engine of development. Emphasis is given to the revival of the local culture with the emergence of small and medium enterprises, along with the motivation of younger populations and women to become active entrepreneurs. However, a more holistic approach should be taken to sustainable tourism development in Cyprus, ensuring that all local communities have an opportunity to develop small-scale niche tourism products that enhance the image of rural destinations and which become a source of pride for the residents. Originality/value The study contributes to the literature by enhancing knowledge of the relationship between tourism and local rural communities. Shedding light on residents' perceptions by evaluating social and environmental impacts can guide government policy making and implementation.
Keywords: Rural areas; Residents’ perceptions; Cyprus; Semi-structured interviews; Sustainability; Impacts